First-principle calculations and experimental investigation on the infrared emissivity property of Mg-doped ZnO. (November 2017) - Guo, Tengchao; Xu, Guoyue; Tan, Shujuan; Liu, Ning; Zhang, Jianchao; Zeng, Xiangxiong; Liang, Juan
Graphical abstract: Highlights: The infrared emissivity of ZnO based materials is calculated by First-principle. The bigger the real part of dielectric function is, the higher the infrared emissivity is. The smaller the conductivity is, the higher the infrared emissivity is. The real part of dielectric function depends on the total polarizability of semiconductor. The conductivity of mainly depends on the electronic properties of semiconductor. Abstract: The electronic properties and infrared emissivity of Zn1-x Mgx O (x = 0, 0.0625, 0.125) were systematically investigated by using the first-principle calculations based on density functional theory (DFT). The Zn1-x Mgx O (x = 0, 0.0625, 0.125) powders were prepared by sol-gel method and their infrared emissivity in the wavelength of 8–14 μm was characterized. The results indicate that the infrared emissivity increases with the increase in Mg concentration, which is attributed to the reduction in conductivity and in the real part of dielectric function. Furthermore, the variation in conductivity and dielectric function has been well studied, and a reasonable method to calculate infrared emissivity of semiconductors has been established. It is expected that this method can be used for designing materials with different infrared emissivity and also applied for effectively guiding the experimental investigation.